Dwarf shrub and grass vegetation resistant to long‐term experimental warming while microarthropod abundance declines on the Falkland Islands. (30th September 2017) - Bokhorst, S.; Convey, P.; Huiskes, A.; Aerts, R.
Abstract: Dwarf shrubs are a dominant plant type across many regions of the Earth and have hence a large impact on carbon and nutrient cycling rates. Climate change impacts on dwarf shrubs have been extensively studied in the Northern Hemisphere, and there appears to be large variability in response between ecosystem types and regions. In the Southern Hemisphere, less data are available despite dwarf shrub vegetation being a dominant feature of southern South America and mountainous regions of the Southern Hemisphere. Here, we present the response of an Empetrum rubrum dwarf shrub and a Poa grass community to 12 years of experimental climate manipulation achieved using open top chambers on the Falkland Islands, a cold temperate island group in the South Atlantic. The dwarf shrub and grass vegetation did not change significantly in cover, biomass or species richness over the 12 years period in response to climate warming scenarios of up to 1°C reflecting annual warming levels predicted in this region for the coming decades. The soil microarthropod community, however, responded with declines in abundance (37%) under warming conditions in the grass community, but no such changes were observed in the dwarf shrub community. Overall, our data indicate that dwarf shrub communities are resistant to the levels of climate warming predicted over the coming decades in the southern South America region and will, therefore, remain a dominant driver of local ecosystem properties.